Pre- and Post-Intervention Effects of Conventional Versus Final Offer Arbitration - Starke, Frederick A.; Notz, William W. (Academy of Management Journal, 1981)
This study investigated the relative impact of final offer (FOA) and conventional (CA) arbitration on bargainers? pre- and post-intervention attitudes and behavior over two rounds of bargaining. Among other results, it was found that in both rounds, subjects anticipating FOA had lower aspirations prior to bargaining and were closer to agreement at the conclusion of bargaining than were subjects anticipating CA.